Типология женских характеров и судеб в произведениях Всеволода Соловьёва о русской истории XVII века - Никольский, Евгений Владимирович; Nikolskiy, Jevgen (Східноєвропейський національний університет імені Лесі Українки, 2016)
В статье рассмотрена типология женских характеров в исторических романах Всеволода Соловьева «Жених Царевны» (1891), «Касимовская невеста» (1879) и «Царь-девица» (1878), посвященных русской истории XVII ст. Проанализирован созданный писателем тип «порушенной невесты» и иные женские типажи. Отмечается, что писатель критически оценивал уклад допетровской Руси, когда талантливые женщины вынуж¬дены были становится затворницами и что искреннее восхищение Всеволода Соловьева вызывали религиозно одаренные натуры, а также бунтарки. Особенно подробно в этом контексте анализируется образ царевны Софьи, которая представлена во всем противоречии и её эпохи, и её натуры (как грешница и как святая). The article deals with Wsevolod Solovyov's (1849–1903) typology of female characters in historical novels «The groom of the princess» (1891), «The bride from Kasimov» (1879) and «The Tsar-maiden» (1878), devoted to Russian history XVII of century. Author analyses the types of «not taken place bride» and other female types created by the writer. The article says that the writer has critically evaluated the structure of pre-Petrine Russia when talented women had become nuns and what sincere admiration Vsevolod Solovyov called religious gifted life, and rebels. In particular, in this context, analyzed the image of the Princess Sophia, which is presented in all its contradiction and its era and its nature (and as a sinner and as a Saint).
The Typology of Female Characters and Destinies in Wsevolod Solovyov's novels about Russian History XVII of a Century
Keywords: исторический роман; XVII век; авторское восприятие исторической личности; династия Романовых; царевна Софья; женские образы; the historical novel; XVII a century; author's perception of the historic figure; Romanov's dynasty; princess Sofia; female images